Metacognitive accuracy differences in Parkinson’s disease and REM sleep behavioral disorder relative to healthy controls - Bălăeţ, Maria; Alhajraf, Falah; Bourke, Niall J.; Welch, Jessica; Razzaque, Jamil; Malhotra, Paresh; Hu, Michele T.; Hampshire, Adam (Frontiers in Neurology, 2024)
Background Metacognition is the ability to monitor and self-assess cognitive performance. It can be impaired in neurodegenerative diseases, with implications for daily function, and the ability of patients to reliably report their symptoms to health professionals. However, metacognition has not been systematically assessed in early-mid stage Parkinson’s disease (PD) and REM sleep behavioral disorder (RBD), a prodrome of PD. Objectives This study aimed to evaluate metacognitive accuracy and self-confidence in PD and RBD patients across various cognitive tasks. Methods We conducted detailed computerized cognitive assessments with 19 cognitive tasks within an established PD and RBD cohort. Participants self-rated their performance post-task. Metacognitive accuracy was calculated by comparing these ratings against objective performance and further analyzed against clinical and mental health factors. Results PD and RBD patients’ metacognitive accuracy aligned with control subjects. However, they exhibited lower confidence across cognitive domains, reflecting their reduced cognitive performance. A notable inverse correlation was observed between their confidence and MDS-UPDRS I and II scales and HADS anxiety and depression scores. Conclusion Our findings indicate that patients with early to mid-stage PD and RBD are generally aware of their cognitive status, differing from other neurological disorders. The inverse relationship between patient confidence and symptoms of depression, anxiety, and daily life challenges underscores the impact of emotional and functional difficulties on their self-perception of cognitive abilities. This insight could be significant for understanding how these conditions affect mental health, aiding clinicians in developing more effective patient care strategies.